Bug reduction with reliability factors using hybrid reliable model - Vijaya Saradhi, T; Manisha, M; Vijaya Lakshmi, L; Gowtham, K (International Journal of Engineering and Technology, 2017)
Software reliability is the probability that software will not cause the failure of a product for a specified time under specified conditions. Software Reliability is also an important factor affecting system reliability. Software reliability is different compared to hardware reliability. Hardware reliability is the one which deals with manufacturing something which is related to external features of the system. Reliability is one of the major problem faced by the systems. Hence, there are some factors which make the system much reliable. As there are different types of software reliable models we analyses each of its performance and also the factors which are affecting them. In this paper we propose a hybrid model which is used for the reduction in the count of bugs and also we implement the reliability factors for that model. Therefore, this model reduces number of bugs. As we know reliability is inversely proportional to the number ofbugs and therefore by using this model we are increasing reliability.